On construction of jet-drop optical measuring systems: analysis of optical, dynamic and metrological parameters in visualization of surface of product - E. V. Leun; L. G. Varepo; A. E. Shakhanov; A. V. Nickel (Омский научный вестник)
The article is devoted to the use of jet-drop optical measuring systems for measuring shape deviations, including surface roughness of products during processing. The issues of image transmission, focal length control due to the merger of several drops of one or more hydraulic streams are considered. The issues of image transmission by moving and falling drops on the surface of the processed product are discussed. The paper presents a method for calculating the performance requirements for registering a microscope image together with a moving droplet, depending on its size, the liquid used and the speed of its movement. The developed method of calculating the positioning error of moving droplets for one – and two-axis control of the trajectory of the droplet flow is considered.